Clinicoetiological profile of neonatal seizures in a tertiary care hospital - Rastogi, S; Rai, Preeti Lata; Prasad, P L (Indian Journal of Child Health, 2017)
Background: Seizure is one of the most frequently observed clinical sign in neonatal period and may be the only sign of a central nervous system disorder. Its recognition is of paramount importance and a newborn with seizures is in a true medical emergency requiring prompt intervention. Objective: To determine the clinical and etiological profile of seizures among neonates admitted to neonatal unit in a tertiary care hospital. Materials and Methods: It was a prospective, observational, hospital-based study conducted over a period of 1 year (December 2014-November 2015). Nearly, 63 babies either admitted with neonatal seizures or who developed seizures after admission were studied to find the clinical and etiological profile. Detailed history including gestational age, mode of delivery, birth events, Apgar scores and antenatal problems, age of onset, and frequency of seizures was also noted. Seizures were classified on the basis of detailed description by pediatric resident on duty in a predesigned pro forma. Informed written consent of parents was taken before enrolling a baby in study. Results: Sepsis was the most common cause of neonatal seizures (64.9%), followed by birth asphyxia, i.e., hypoxic ischemic encephalopathy (HIE) (48.3%). Hypoglycemia was seen in 21.6% and hypocalcemia in 18.3% cases. Subtle seizures were the most common type of seizures seen in 65% babies, followed by tonic (31.6%), myoclonic (16.6%%), and clonic (6.67%) type. Subtle seizures were commonly seen in cases of HIE. Conclusion: The recognition of clinicoetiology of neonatal seizures is often helpful with respect to prognosis and treatment. The most common etiology for neonatal seizure is sepsis. Onset of seizures during first 3 days of life has significant correlation with HIE as etiology. Subtle seizures are the most common type of clinical seizures, which is difficult to identify; therefore, careful observation of at risk newborns is necessary.